Writing 'that animal darkness': Galway Kinnell, Gary Snyder, James Merrill - Hoorenman, Johanna (School of English, 2016)
As humanity’s most evident other, at once deeply similar to and fundamentally different from the human, the animal is a valuable poetical trope. This thesis examines the representation and function of animals and animality in the writings of three key late twentieth-‐century American poets: Galway Kinneell, Gary Snyder and James Merrill. The first chapter outlines an historical and theoretical context of the notion of the representation of animals in human culture in general and in American literature in particular. The subsequent three chapters provide close readings and stylistic and thematic discussions of the animal poems of Kinnell, Snyder, and Merrill, respectively. In Theory of Religion, George Bataille argues that animal life is intrinsically closed off from human understanding as it lacks precisely that which is essential to understand it: consciousness. Only when making a “poetic leap,” can one look at the animal as not simply a thing, and begin to “[extend a] glimmer into that animal darkness.” However, what can be described as animal poetry is not necessarily always poetry about animals but poems in which the animal subjects or images are invoked for their metaphorical potential and employed to express something about the human experience. This difference in types of animal poetry should not be seen as an opposition but as a sliding scale or a continuum of metaphoricity: animals in poetry are rarely entirely observations, imaginations or representations of real, living animals on the one hand, and purely metaphorical tools on the other. This study employs a methodology of close reading of poems with attention to underlying assumptions and cultural conventions within these texts. Rather than divide animal poems or animal poetic subjects into categories of real or metaphorical or wild and domesticated, the study looks at representation of the animal subject and the meaning and function that it has within the context of the poem. Although the subjects and issues that are examined will thus inevitably alter according to which poem is being read, some concerns persist throughout. While this discussion focuses on animals, each poet’s animal poems are placed in the wider context of the poet’s poetic engagement with nature in general, and with the interpretation of human-‐nature and human-‐animal dichotomies present in their work. Chief amongst these is the notion of a continuum of metaphoricity on which these poems may be located, and the question of whether the animal is representing something about its own, animal experience or about a human experience. Other recurring concerns are those of anthropocentrism, anthropomorphisation, and questions of kinship and otherness. By exploring the animal poems of Kinnell, Snyder and Merrill through close readings of their animal poems and a detailed discussion of the main themes and approaches in their efforts to ‘write animals,’ this study contributes new and original approaches to each of these poets’ works, discussing their treatment of animal subjects within the wider context of their individual poetics and providing a unique perspective on the relationship between their poetic universe and the external world. Moreover, this study forms a first step towards a comprehensive critical examination of the ways in which American poets engage with the rich fauna of their continent and of the efforts they make towards illuminating “that animal darkness.
Keywords: Poetry